Medical Emergency During Flight: A Team-Building Exercise - Jeff Pettit (Association of American Medical Colleges, 2017)
Introduction While teams are a central component in health care, many professionals who function in them have had little, if any, formal training on how to develop an effective team. Medical educators and trainers have used many different approaches to teach the basic skills and knowledge of team effectiveness and how team members can best interact with each other. To make team training more realistic, experiential exercises have been used. One of the more popular categories of experiential activities is survival exercises in which team members are given a scenario and required to make decisions that ultimately decide whether the team survives the ordeal. Methods This activity describes a situation in which a medical professional is traveling on an airliner when a request for medical assistance occurs. Participants can include clinically experienced medical students, residents, fellows, and faculty physicians. The activity can be used as a stand-alone exercise or in conjunction with another team topic, such as communications or decision making. It has also been effective as an icebreaker for teams working together during a workshop. Results Approximately 100 medical students, residents, and faculty from anesthesia, family medicine, pediatrics, and internal medicine have participated in this activity. It has been very well received and generated a great deal of discussion of both medical knowledge and team-building skills. Discussion This activity, which can be used to examine team communications, decision making, leadership, and conflict management, is suitable for health care professionals either through intra- or interprofessional training.